PENGARUH KUALITAS LAYANAN TERHADAP KEPUTUSAN KONSUMEN DALAM PEMILIHAN PERUSAHAAN JASA PEMBIAYAAN KREDIT - Sampeliling, Alexander (FORUM EKONOMI, 2015)
The purpose of this research is to know how much the quality service effects the customers decision in choosing service company and credit funding at PT Finansia Multi Finance Samarinda. The Population of this Research is all of the customers men and women who attain the age of more than 18 years old and ever bought motorcycle by credit at PT Finansia Multi Finance Samarinda as many as 150 samples. The analysis method of this research is the multiple linear regression analysis method and the result of the research, three is the influence of quality service tangibles, reliability, responsiveness, assurances and empathy partially and simultaneously to customers decision in choosing service Company and credit. Keywords: The quality of service, Costumers decision in choosing.